The BCG shortage – what isn't the fuss about?. Issue 4 (27th July 2016) - Modgil, Vaibhav; Cashman, Sophia; Gommersall, Lyndon
Abstract : A recent widespread shortage of BCG supplies in the UK has resulted in many patients receiving suboptimal doses of BCG or alternative treatment regimens that may not be as effective. The authors consider the lack of media interest in the issue and look at the potential solutions to the problem.